Effects of silver nanoparticles (NM‐300K) on Lumbricus rubellus earthworms and particle characterization in relevant test matrices including soil. (April 2014) - van der Ploeg, Merel J.C.; Handy, Richard D.; Waalewijn‐Kool, Pauline L.; van den Berg, Johannes H.J.; Herrera Rivera, Zahira E.; Bovenschen, Jan; Molleman, Bastiaan; Baveco, Johannes M.; Tromp, Peter; Peters, Ruud J.B.; Koopmans, Gerwin F.; Rietjens, Ivonne M.C.M.; et al.
Abstract The impact of silver nanoparticles (AgNP; at 0 mg Ag/kg, 1.5 mg Ag/kg, 15.4 mg Ag/kg, and 154 mg Ag/kg soil) and silver nitrate (AgNO3; 15.4 mg Ag/kg soil) on earthworms, Lumbricus rubellus, was assessed. A 4‐wk exposure to the highest AgNP treatment reduced growth and reproduction compared with the control. Silver nitrate (AgNO3) exposure also impaired reproduction, but not as much as the highest AgNP treatment. Long‐term exposure to the highest AgNP treatment caused complete juvenile mortality. All AgNP treatments induced tissue pathology. Population modeling demonstrated reduced population growth rates for the AgNP and AgNO3 treatments, and no population growth at the highest AgNP treatment because of juvenile mortality. Analysis of AgNP treated soil samples revealed that single AgNP and AgNP clusters were present in the soil, and that the total Ag in soil porewater remained high throughout the long‐term experiment. In addition, immune cells (coelomocytes) of earthworms showed sensitivity to both AgNP and AgNO3 in vitro. Overall, the present study indicates that AgNP exposure may affect earthworm populations and that the exposure may be prolonged because of the release of a dissolved Ag fraction to soil porewater. Environ Toxicol Chem 2014;33:743–752. © 2013 SETAC